Issues in values-based education in Malaysia - Hashim, Che Noraini (IIUM Press, 2014)
This book is based on research work, papers presented at national and international conferences and articles written by the author and her colleagues. It covers a wide range of topics that are intended to open up new horizons on how certain developments of Islamic based education and contemporary issues should be perceived and discussed. This book should serve as a guide and reference for educators and students to enhance their understanding of matters affecting values based perspectives. This book is divided into two parts. Part I incorporates the Prophet’s (p.b.u.h) pedagogy, issues related to Islamic based curriculum, and the role of educational institutions in creating barriers or building bridges between the Muslim World and the West. Part II provides discussions and findings on issues in values-based education. Some suggestions are put forward at the end of each chapter as remedial measures and to reach the cherished goals for further discussions in classroom.